PERTANGGUNG JAWABAN PIDANA DEBT COLLECTOR YANG MELAKUKAN KEKERASAN DALAM PENAGIHAN UTANG - Lologau, Rudy (JURNAL ILMU HUKUM TOPOSANTARO, 2025)
This type of research is empirical research, namely research with field data as the main data source, such as the results of interviews and observations. The conclusion in this study: The factors that cause debt collectors to commit violence in debt collection consist of institutions that are too pursuing targets, lack of awareness of debtors, lack of legal knowledge of third parties or debt collectors and debtors, then influenced by the characteristics of debt collectors. The criminal liability of debt collectors who commit criminal acts in the form of violence against debtors is individual responsibility, criminal acts committed by debt collectors include the crime of coercion (Article 335 of the Criminal Code), forcibly confiscating customer goods which can be indicated as the crime of theft (Article 362 of the Criminal Code), the crime of extortion with violence (Article 368 of the Criminal Code), and the crime of forcing people with threats of defamation (Article 369 of the Criminal Code). Without having anything to do with companies that use debt collectors in carrying out penagi-han. However, if the company or financing institution uses the services of a debt collector and authorizes the debt collector to collect debts by using violence, the company can be held liable under (Article 55 of the Criminal Code). Jenis penelitian ini adalah penelitian empiris. yaitu penelitian dengan adanya data-data lapangan sebagai sumber data utama, seperti hasil wawancara dan observasi. Kesimpulan dalam penelitian ini: Faktor penyebab debt collector melakukan kekerasan dalam penagihan utang yaitu terdiri atas lembaga terlalu mengejar target, kurangnya kesadaran debitur, kurangnya pengetahuan hukum pihak ketiga atau debt collector dan debitur, kemudian dipengaruhi oleh karakteristik debt collector. Pertanggungjawaban pidana debt collector yang melakukan tindak pidana berupa kekerasan terhadap debitur adalah tanggung jawab secara individu, tindak pidana yangdilakukan oleh debt collector diantaranya adalah tindak pidana pemaksaan (Pasal 335 KUHP), menyita paksa barang nasabah yang dapat terindikasi sebagai tindak pidana pencurian (Pasal 362 KUHP), tindak pidana pemerasan dengan kekerasan (Pasal 368 KUHP), dan tindak pidana memaksa orang dengan ancaman pencemaran nama baik (Pasal 369 KUHP). Tanpa ada kaitannya dengan perusahaan yang menggunakan jasa debt collector dalam melakukan penagihan. Tetapi, apabila pihak perusahaan atau pihak lembaga pebiayaan yang menggunakan jasa debt collector dan memberikan kuasa kepada debt collector untuk menagih utang dengan memakai cara kekerasan maka pihak perusahaan dapat dipertanggungjawabkan berdasarkan (Pasal 55 KUHP).